Power Generation Performance of a Pilot-Scale Reverse Electrodialysis Using Monovalent Selective Ion-Exchange Membranes - Mehdizadeh, Soroush (Membranes (Basel), 2021)
Reverse electrodialysis (RED) is a promising process for harvesting energy from the salinity gradient between two solutions without environmental impacts. Seawater (SW) and river water (RW) are considered the main RED feed solutions because of their good availability. In Okinawa Island (Japan), SW desalination via the reverse osmosis (RO) can be integrated with the RED process due to the production of a large amount of RO brine (concentrated SW, containing ~1 mol/dm(3) of NaCl), which is usually discharged directly into the sea. In this study, a pilot-scale RED stack, with 299 cell pairs and 179.4 m(2) of effective membrane area, was installed in the SW desalination plant. For the first time, asymmetric monovalent selective membranes with monovalent selective layer just at the side of the membranes were used as the ion exchange membranes (IEMs) inside the RED stack. Natural and model RO brines, as well as SW, were used as the high-concentrate feed solutions. RW, which was in fact surface water in this study and close to the desalination plant, was utilized as the low-concentrate feed solution. The power generation performance investigated by the current-voltage (I–V) test showed the maximum gross power density of 0.96 and 1.46 W/m(2) respectively, when the natural and model RO brine/RW were used. These are a 50–60% improvement of the maximum gross power of 0.62 and 0.97 W/m(2) generated from the natural and model SW, respectively. The approximate 50% more power generated from the model feed solutions can be assigned to the suppression of concentration polarization of the RED stack due to the absence of multivalent ions.